Piezo-enhanced photocatalytic performance of ZnO nanorod array for pollutants degradation in dynamic water: insight into the effect of velocity and inner flow field - Wen, Yingying (2023)
The piezoelectric effect, which can promote photocatalytic degradation of pollutants, has attracted great attention. However, the effect of hydrodynamic factors on the performance is still unclear in the water-driven piezo-enhanced photocatalytic process. Herein, ZnO nanorod array on porous substrate was employed to study the effect of hydrodynamic factors on piezo-assisted photocatalysis. Flow field simulation analysis based on computational fluid dynamics (CFD) indicates that velocity notably affects the piezo-photocatalytic process. Meanwhile, the porous structure of substrate promotes the formation of micro-turbulence, which also significantly improve the piezopotential of ZnO and further enhance the catalytic performance. Density functional theory (DFT) calculations further reveal the vulnerable sites attacked by reactive species, thereby proposing the possible degradation pathway of pollutant. This study illustrates the important role of hydrodynamic factors in piezo-photocatalytic process and provides a feasible way for in-situ purification of pollutants in urban sewerage and drainage.